A Stability Indicating Liquid Chromatography Method for the Assay of Rufinamide Bulk Material and Tablets (The East and Central African Journal of Pharmaceutical Sciences, 2018)
A simple, rapid, isocratic stability indicating reverse phase liquid chromatography method was developed for the assay of rufinamide bulk drug and tablets. The method achieved adequate resolution of rufinamide, related substances A and B as well as laboratory generated degradation products. The method uses a Phenomenex® Hyperclone BDS C-18 column (250 × 4.6 mm, 5 μ) maintained at 35 °C and a mobile phase composed of methanol-0.1 M octane sulfonic acid-0.1 M KH2PO4, pH 6.5-water (30:10:5:55, % v/v/v/v) delivered at a flow rate of 1.0 ml/min. The eluents were monitored by means of ultraviolet detection at 210 nm. During validation, the method satisfied the International Conference on Harmonization acceptance criteria for linearity sensitivity, precision, accuracy, and robustness. The developed method may be applied in the routine analysis of rufinamide bulk material and tablets as well as stability studies.
Keywords: Rufinamide; stability indicating method; related compound